The guiding function of the image in the experience of Wafa Abdul Razzaq poetry: (Do not hesitate to cast crystals) model - Mohamed Lazzam, Alaa; mahmoud hussein, kawakib (Al-Adab Journal, 2020)
And this is what we try to detect and revealed in a new reading and different experience of the Iraqi poet Almgujp from the inside of the pain of her homeland, which was surrounded by the forces of demolition and the courtyard and the void became a playground in which to fight, and fights on the cloves of Henna with the blood of his sons wolves jungle, poet watching this demolition hurts from the inside Vnrsd Refraction sometimes and sometimes the revelation in a realistic vision to reveal the silent about him, and cover hidden and hidden behind the cloak of religion and doctrine and party.Through our study of the image orientation function in the poet's office, we found that the effectiveness of the image stems from within the poetic text through four main elements: Its ability to direct the recipient based on its components, which includes the image material and its content, and the way the images in which our poet originated are formed the strength of the emergence of images and its emergence has been adopted poet in her office to the image in a large and strong. the ability of the poet to combine antagonisms and invest in the correspondence of the senses and the intensification of the symbolic image and support arguments to convince the recipient of the important and fundamental thing in the direction of improvement or justification.